The Effect of Financial Incentives, Organizational Commitment, and Job Satisfaction on Employee Performance - Rahmadi, Doddy Firman; Partiwi, Sri Gunani (Institut Teknologi Sepuluh Nopember, 2020)
Organization or business performance always have close relation with its own member or employee performance and productivity. Most of them only focus on raising the wealthy of its member by giving financial incentives hoping it will reflect with significant improvement of member performance. But in some case giving the incentives not always bring significant increase to member productivity. This study was made with the aim to determine the effect of financial incentives, organizational commitment, and job satisfaction on employee performance. This study uses quantitative study. Data collection procedures used in this study are structured data collection. The population used is 10 persons of installation and maintenance employees of PT. KONE Indo Elevator throughout Indonesia that has implement some financial incentive to boots up their employee performance. The result of the study was financial incentives and job satisfaction have positif and significant effect to employee performance while organizational commitment not having signifficant effect to employee performance.